Pengaruh Profitabilitas, Likuiditas, Leverage Terhadap Nilai Perusahaan pada Perusahaan Properti Yang terdaftar Di Bursa Efek Indonesia - Zahra, Rani; Savitri, Aulia Diana; Violeta, Elice (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
This research aims to analyze the influence of profitability, liquidity also leverage on company value in property companies listed on the Indonesia Stock Exchange(BEI)for the 2019-2023 period. Profitability is measured using Return on Assets(ROA), Liquidity is measured using Current Ratio(CR), also Leverage is measured using Debt to Equity Ratio(DER), Company value is measured using Price to Book Value(PBV). This research uses quantitative research methods. The population of this research is all property companies registered on the IDX for the 2019-2023 period, namely 18 companies. The sample selection in this study used purposive sampling with certain criteria so that 5 data samples were obtained for research. The data used is secondary data obtained from financial reports on the IDX. The data analysis technique uses multiple linear regression analysis. This research shows that profitability has a positive also significant effect on company value, liquidity has an insignificant negative effect on company value, also leverage has an insignificant positive effect on company value.